MEDIATION AS A SETTLEMENT OF ELECTRONIC BOOK COPYRIGHT DISPUTES TO PROVIDE LEGAL CERTAINTY FROM A BENEFIT PERSPECTIVE - Waruwu, Khamozaro; Eddy, Triono; Mansar, Adi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The use of mediation as an effort to resolve electronic book copyright disputes has become a trend in the community to utilize dispute resolution based on several factors that place it with various advantages, including economic factors, legal culture factors, the wide scope of problems that can be discussed, coaching factors. good relations between the parties and process factors. Based on this, it has become a necessity that mediation is no longer an alternative dispute resolution but rather a dispute resolution effort that must be taken if there is a violation of electronic book copyright. This is in line with the great interest in mediation as an effort to resolve electronic book disputes in providing legal certainty and various perspectives on the benefits of mediation. The purpose of writing is to discuss mediation as an alternative resolution of electronic book copyright disputes. Intellectual Property Rights are referred to as material rights, and the results of this work can be in the form of immaterial objects "intangible objects" which originate from the work of the brain and the results of the work of reasoning ratios which give rise to intellectual property rights. The Copyright Law, especially in Article 40 Paragraph (1) letter n, implicitly recognizes that digital or electronic books (e-books) are one of the adapted works that receive protection. Even though the Copyright Law provides legal guarantees or protection to copyright, creators and copyright holders, in its implementation there are still irregularities in the field of copyright and perpetrators of copyright irregularities can be legally prosecuted. Mediation is a type of dispute resolution that can be chosen in resolving issues in the field of IPR, especially regarding e-book piracy disputes which are currently widespread. This research uses a normative juridical research method with two types of approaches, namely the statutory research approach and the case research approach. Mediation is the most effective alternative dispute resolution and is required for copyright disputes because it is regulated in the Copyright Law. Apart from this, the form of dispute resolution through mediation has other advantages in the form of being completed more quickly, being lighter, having lower costs and satisfying both parties